Orbital prefrontal cortex volume correlates with social cognitive competence. - Powell, J; Lewis, P; Dunbar, R; García-Fiñana, M; Roberts, N (2010)
Intentionality, or Theory of Mind, is the ability to explain and predict the behaviour of others by attributing to them intentions and mental states and is hypothesised to be one of several social cognitive mechanisms which have impacted upon brain size evolution. Though the brain activity associated with processing this type of information has been studied extensively, the neuroanatomical correlates of these abilities, e.g. whether subjects who perform better have greater volume of associated brain regions, remain to be investigated. Because social abilities of this type appear to have evolved relatively recently, and because the prefrontal cortex (PFC) was the last brain region to develop both phylogenetically and ontogenetically, we hypothesised a relationship between PFC volume and intentional competence. To test this, we estimated the volume of four regional prefrontal subfields in each cerebral hemisphere, in 40 healthy adult humans by applying stereological methods on T(1)-weighted magnetic resonance images. Our results reveal a significant linear relationship between intentionality score and volume of orbital PFC (p=0.01). Since this region is known to be involved in the processing of social information our findings support the hypothesis that brain size evolution is, at least in part, the result of social cognitive mechanisms supporting social cohesion.